1991
DOI: 10.1210/endo-129-6-3174
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone Antagonizes the Suppressive Effects of Dexamethasone on Lymphocyte Proliferation*

Abstract: Administration of dehydroepiandrosterone (DHEA) appears to have physiological effects opposing those of glucocorticoids in several animal models. Recently, immunomodulatory effects of treatment with DHEA have been described. This paper reports the effects of DHEA treatment on splenocyte blastogenic responses as well as thymic and spleen weights in C3H/HeN mice. Pretreatment of mice with sc DHEA (60 mg/kg.day) for 3 days in vivo antagonized the profound suppression of in vitro blastogenic responses seen in T- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(96 citation statements)
references
References 32 publications
3
93
0
Order By: Relevance
“…Plasma levels of DHEA peak in early adulthood (reaching levels of 2-4 ng/ml) and then decline through adult life (9). In adult mice, DHEA levels are ϳ1 ng/ml and they dramatically increase following parental administration of DHEA (32). In the present investigation, the A, PCR products were visualized in a 1.5% agarose gel containing 0.5 g/ml ethidium bromide; B, Levels of each target mRNA were measured by a digital image system and were presented after they were normalized with the internal control GAPDH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma levels of DHEA peak in early adulthood (reaching levels of 2-4 ng/ml) and then decline through adult life (9). In adult mice, DHEA levels are ϳ1 ng/ml and they dramatically increase following parental administration of DHEA (32). In the present investigation, the A, PCR products were visualized in a 1.5% agarose gel containing 0.5 g/ml ethidium bromide; B, Levels of each target mRNA were measured by a digital image system and were presented after they were normalized with the internal control GAPDH.…”
Section: Discussionmentioning
confidence: 99%
“…NF-B consensus oligonucleotide (5Ј-AGTTGAGGG GACTTTCCCAGGC-3Ј) was purchased from Promega (Madison, WI), and nuclear factor-Y box binding (NF-Y) oligonucleotide (5Ј-GATCT GAGAATTTTCTGATTGGTTCTGGCGAGTTTGG-3Ј) (27) was synthesized at IDT (Coralville, IA) and purified by polyacrylamide gel. Doublestranded oligonucleotide probe was labeled by 32 P in a reaction containing 2 l of probe (3.5 pmol), 1 l of T4 polynucleotide kinase buffer (10ϫ),…”
Section: Nuclear Extraction and Emsamentioning
confidence: 99%
“…8 DHEA was also reported to antagonize the suppressive effects of dexamethasone on T-and B-lymphocyte proliferation in mice. 59 T lymphocytes are known to be present and to play a certain role in atherosclerosis 60 ; however, that role has not been fully established. Although the population and distribution of T cells in an atherosclerotic lesion after DHEA treatment did not show any change in our preliminary observations, the possibility of an antiatherosclerotic effect of DHEA through the receptor-mediated system of activating T lymphocytes remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…DHEA, however, promotes production of IL-2 (a Thl cytokine) by activated murine T cells, and reverses the suppression of blastogenic responses and IL-2 production initiated by corticosteroids (1,5). A recent study has also shown that low levels of DHEA (100 nM down to 10 pM) can synergize with lipopolysaccharide, to increase the production of the inflammatory cytokines IL-1 and tumor necrosis factor a (TNFa) by human macrophages in vitro (6).…”
mentioning
confidence: 99%